ANALISA STRUKTUR BAWAH PERMUKAAN DAERAH PROSPEK PANAS BUMI “GF-TNH” SUMATERA BARAT BERDASARKAN METODE GAYA BERAT - Ramadhan, Adi Buchori; Djayus, Djayus; Lepong, Piter (GEOSAINS KUTAI BASIN, 2020)
The gravity method is one of the geophysical exploration methods based on the Earth's gravity field anomaly caused by variations in rock mass density laterally and vertically below the measuring point. The study area has a range of complete bouguer anomaly of -48.3 mGall up to -4.0 mGall and depth estimation with spectrum analysis showing a regional anomaly depth value of 2.43 km and a residual anomaly depth of 0.77 km which is interpreted as a boundary zone between bedrock and subsurface rocks that have more varied anomaly values. Then the separation of regional and residual anomaly was carried out using the Butterworth Filter and Second Vertical Derivative methods. From the results of the residual anomaly map shows the range of anomaly values ​​-0.5 mGall to 4.0 mGall. The map of residual anomaly shows a more complex pattern of anomaly because residual anomaly provide a lateral representation of rock mass distribution or the presence of geological structures below the surface that are relatively close to the surface of the earth. Then the residual anomaly map is made 3D inversion modelling with Second Vertical Derivative Technique to find out the fault and its type, then Derivative Analysis is performed. The geological structure in the study area is based on the results of inversion modelling and derivative analysis, dominated by faults and the type of fault is reverse fault and normal fault and the type of rock is dominated by igneous rock which has a high density value.